Molecular spectroscopy-- XI : specially invited lectures presented at the eleventh European Congress on Molecular Spectroscopy held at Tallinn, USSR, 28 May-1 June 1973 (Butterworths, 1974)
Molecular Spectroscopy-XI provides information pertinent to the fundamental aspects of molecular spectroscopy. This book discusses the modifications of molecular spectra when the density varies as a function of temperature and pressure. Organized into 15 chapters, this book begins with an overview of the several processes concerning triplet excitons leading to magnetic-field sensitive luminescence in organic crystals and related compounds. This text then examines the methods of investigation of the exciton band structures in molecular crystals. Other chapters consider the conditions for the eq.